Fractional order integral and derivative (FOID) controller with anti-windup for temperature profile control - Pandey S.; Soni N.K.; Pandey R.K. (My University, 2025)
This paper establishes a new strategy for temperature profile control with the help of fractional order PI and PID controller. The idea of using a fractional order controller is not new for the first order plus time delay (FOPDT) systems but by introducing an anti windup scheme with fractional order controller the performance of the system can be increases significantly. As we know all processes are subjected to constraints in practice and the actuators have a limited range of action like in op-amp based controller (+vcc to -vcc) those who bound the controller output with in some specified range. So the use of anti-windup scheme with fractional order integral and derivative (FOID) controller will be more effective when the saturating elements will come in to the picture. Thus the main purpose of this paper is to examine the performance of two different fractional order controllers (with and without anti-windup scheme) for temperature profile control. From experimental comparisons with the traditional fractional order integral and derivative(FOID) controller based on Ziegler-Nicholas' tuning method, it will be shown that the proposed methodologies are specifically beneficial in controlling temperature in time-delay heat flow systems with saturating element. © 2015 IEEE.